Social Dynamics Management and Functional Behavioral Assessment. (March 2018) - Lee, David L.
Managing social dynamics is a critical aspect of creating a positive learning environment in classrooms. In this paper three key interrelated ideas, reinforcement, function, and motivating operations, are discussed with relation to managing social behavior.